Personhood and partialism in African philosophy. Issue 3 (3rd July 2019) - Molefe, Motsamai
ABSTRACT: This article ascertains what philosophical implications can be drawn from the moral idea of personhood dominant in African philosophy. The article aims to go beyond the oft-made submission that this moral idea of personhood is definitive of African moral thought. It does so by advancing discourse with regard to personhood by exploring its relationship with another under-explored idea in African ethics, the idea of partialism. The article ultimately argues that the idea of personhood can be associated with two (related) sorts of partialisms: agent-related and other-centred partialisms.